Judicial Interpretations and Societal Realities: Muslim Women’s Divorce Rights in Indonesia and Thailand - Jaenal Arifin; Inna Fauziatal Ngazizah; Abdul Rasyid Hameeyae; Abdulroman Mahir (UIN Sunan Kalijaga Yogyakarta, 2026)
Although Islamic family law formally guarantees post-divorce rights for Muslim women, substantial disparities persist in the realization of these rights across different socio-legal contexts. This contradiction is evident in Indonesia and Southern Thailand, where formal legal protections coexist with social, cultural, and institutional barriers that continue to limit women’s access to justice after divorce. This study aims to examine how judicial interpretation and societal realities shape the protection of Muslim women’s post-divorce rights in both jurisdictions. This qualitative research employs a comparative socio-legal approach using legal documents, court decisions, institutional records, field observations, and semi-structured interviews with judges, officials of the Islamic Religious Council (MAI), women’s rights activists, advocates, and former litigants. Data were collected through document analysis, interviews, and non-participant observation, and analyzed using thematic qualitative analysis, juridical-normative analysis, and cross-country comparative analysis. The findings reveal that judges in Indonesia tend to interpret women’s post-divorce rights within a rights-based judicial framework, enabling courts to actively order and enforce maintenance, child support, and other post-divorce obligations. By contrast, religious authorities in Southern Thailand prioritize mediation and communal reconciliation, resulting in greater dependence on voluntary compliance and informal religious legitimacy rather than judicial enforcement. The study further identifies three interconnected mechanisms restricting women’s access to justice across both jurisdictions: patriarchal social norms, institutional fragmentation between legal and religious authorities, and women’s limited legal literacy and economic bargaining power. These findings contribute to comparative socio-legal scholarship by demonstrating that the effectiveness of post-divorce rights protection depends not only on legal norms but also on judicial interpretation and the interaction between legal institutions and local socio-cultural structures. Future research may further investigate Muslim women’s lived experiences across diverse plural legal systems. Meskipun hukum keluarga Islam secara formal menjamin hak-hak perempuan Muslim pasca-perceraian, masih terdapat ketimpangan yang signifikan dalam pemenuhan hak-hak tersebut di berbagai konteks sosio-yuridis. Kontradiksi ini terlihat jelas di Indonesia dan Thailand Selatan, di mana perlindungan hukum formal berdampingan dengan hambatan sosial, budaya, dan kelembagaan yang terus membatasi akses perempuan terhadap keadilan setelah perceraian. Penelitian ini bertujuan untuk mengkaji bagaimana interpretasi yudisial dan realitas sosial membentuk perlindungan hak-hak perempuan Muslim pasca-perceraian di kedua yurisdiksi tersebut. Penelitian kualitatif ini menggunakan pendekatan sosio-hukum komparatif dengan memanfaatkan dokumen hukum, putusan pengadilan, catatan kelembagaan, observasi lapangan, serta wawancara semi-terstruktur dengan hakim, pejabat Majelis Ulama Indonesia (MAI), aktivis hak-hak perempuan, advokat, dan mantan pihak yang berperkara. Data dikumpulkan melalui analisis dokumen, wawancara, dan observasi non-partisipan, kemudian dianalisis menggunakan analisis kualitatif tematik, analisis yuridis-normatif, serta analisis komparatif lintas negara. Temuan penelitian menunjukkan bahwa hakim di Indonesia cenderung menafsirkan hak-hak perempuan pasca-perceraian dalam kerangka yudisial berbasis hak, yang memungkinkan pengadilan untuk secara aktif memerintahkan dan menegakkan kewajiban nafkah, tunjangan anak, serta kewajiban pasca-perceraian lainnya. Sebaliknya, otoritas keagamaan di Thailand Selatan memprioritaskan mediasi dan rekonsiliasi komunal, sehingga lebih mengandalkan kepatuhan sukarela dan legitimasi keagamaan informal daripada penegakan hukum. Studi ini selanjutnya mengidentifikasi tiga mekanisme yang saling terkait yang membatasi akses perempuan terhadap keadilan di kedua yurisdiksi tersebut: norma sosial patriarkal, fragmentasi kelembagaan antara otoritas hukum dan keagamaan, serta literasi hukum dan daya tawar ekonomi perempuan yang terbatas. Temuan-temuan ini berkontribusi pada kajian sosiologis-hukum komparatif dengan menunjukkan bahwa efektivitas perlindungan hak pasca-perceraian tidak hanya bergantung pada norma-norma hukum, tetapi juga pada interpretasi yudisial serta interaksi antara lembaga-lembaga hukum dan struktur sosio-budaya lokal. Penelitian di masa depan dapat menyelidiki lebih lanjut pengalaman hidup perempuan Muslim di berbagai sistem hukum yang pluralistik.